On the history of the armenian notation - Hakobyan, Diana (History and Culture, 2026)
The article aims at presenting the historical development and scholarly exploration of the Armenian symbolic writing systems. It becomes evident throughout the article that the historiography of symbolic writing has remained notably under-researched.The principal conclusion of the study is that the Symbolic Script Codex (“nshanagir imastnots”) has not vanished from the annals of history, yet it has not been subjected to in-depth academic scrutiny and scholarly inquiry. Only a few scholars, namely A. Abrahamyan and H. Acharian, have approached the subject with genuine academic rigor, whereas others have neglected to examine it through a consistent methodological framework.The relevance of this article is underscored by its applicability to several unresolved historical and political issues, particularly as documentary evidence in the fight against cultural plunder. In the modern era, distortions and falsifications of Armenian history have intensified. Countering this phenomenon requires not only the publication of academic studies, but also the revelation and reexamination of historical facts and primary sources that have survived from antiquity.To ensure the purposefulness of the research, primary historical sources authored by chroniclers and data from previous academic investigations were examined. The study was grounded in rare manuscript codices from the Mesrop Mashtots Institute of Ancient Manuscripts (Matenadaran), with special focus on symbolic scripts recorded by medieval scribes. Based on central archival catalogues, 52 manuscript codices containing symbolic scripts were identified and registered.Armenian symbolic writing constitutes one of the essential components of the Armenian nation’s cultural heritage, with origins traceable to the pre-alphabetic era. This writing system, which has undergone transformations and reformulations over time, has fulfilled communicative, ritualistic, ceremonial, and cultural functions. The article examines the historical foundations of symbolic script emergence, their usage across various historical epochs, and their influence on the later development of the Armenian writing system. Special attention is devoted to the application of symbolic writing in religious and ceremonial contexts and its role in the preservation and transmission of national identity. The study reveals that although symbolic writing was ultimately replaced by the alphabet devised by Mesrop Mashtots, it continues to constitute a significant component of the Armenian cultural legacy and remains a subject worthy of renewed scholarly attention and analysis.
Keywords: writing; symbolic script codex (“nshanagir imastnots”); History of Armenia; historical period; culture; manuscript codices